Venom by rick remender, volume 1 ebook - Remender, Rick (Venom (2011), 2012)
Collects Venom (2011) #1-5. America...meet your newest Hero! The lethal alien symbiote known as Venom is in the custody of the U.S. military…and with a familiar face from Spider-Man's world inside the suit, the government's own personal Spidey is going into action as one of the nation's top covert agents in hostile territory!